America First, Third Offset Second?. Issue 4 (4th July 2018) - Fiott, Daniel
Abstract : In 2014, the US Department of Defense announced that it would embark on a new defence innovation initiative termed the 'Third Offset Strategy'. This Obama-era strategy was conceived to overcome the perceived military-technological rise of states such as China, Russia, Iran and North Korea. Since the election of President Donald Trump, however, questions about the continued relevance of the Third Offset Strategy have emerged. Daniel Fiott considers the factors that are driving forward defence innovation efforts in the US under the current administration, and the challenges of doing so.